Answer:
f'(x)![=2(e^4^x)+(x^2+1)(4e^4^x)](https://tex.z-dn.net/?f=%3D2%28e%5E4%5Ex%29%2B%28x%5E2%2B1%29%284e%5E4%5Ex%29)
Step-by-step explanation:
The derivative of the function:
![(x^2+1)e^4^x](https://tex.z-dn.net/?f=%28x%5E2%2B1%29e%5E4%5Ex)
The rule for the product of two functions:
f'(x)![=g'(x)h(x)+g(x)h'(x)](https://tex.z-dn.net/?f=%3Dg%27%28x%29h%28x%29%2Bg%28x%29h%27%28x%29)
Therefore
g(x)![=x^2+1](https://tex.z-dn.net/?f=%3Dx%5E2%2B1)
g'(x)![=2](https://tex.z-dn.net/?f=%3D2)
f(x)![=e^4^x](https://tex.z-dn.net/?f=%3De%5E4%5Ex)
f'(x)![=4e^4^x](https://tex.z-dn.net/?f=%3D4e%5E4%5Ex)
f'(x)![=2(e^4^x)+(x^2+1)(4e^4^x)](https://tex.z-dn.net/?f=%3D2%28e%5E4%5Ex%29%2B%28x%5E2%2B1%29%284e%5E4%5Ex%29)
The sum of 7-1 and 7-2 will be a rational number because sum of rational numbers is a rational numbers.
A rational number is a number which can be written in p/q form where q≠0.
We know that when two rational numbers is added then the sum is also a rational number. And when two rational numbers are subtracted then the difference is also a rational number.
So in the given question, lets study the term differently that is,
i) 7 - 1 is a rational number because their difference is equal to 6 and it can be written in p/q form which is 6/1.
ii) 7 – 2 is also a rational number as their difference will be 5 which is a rational and can be written in p/q form which is 5/1.
So when these two rational numbers are added their sum will also be a rational number which is 11.
Learn more about rational numbers here : brainly.com/question/12088221
#SPJ9
The outlier is the piece of data that does not fit the general data set. In this case, 46 is much higher than all of the other numbers. This is the outlier.
Answer:
2 ounces are in 2 ounces
Step-by-step explanation:
Answer:
<h2>49</h2>
Step-by-step explanation:
Use PEMDAS:
P Parentheses first
E Exponents (ie Powers and Square Roots, etc.)
MD Multiplication and Division (left-to-right)
AS Addition and Subtraction (left-to-right)
==============================================
(-5)² - 2 × (-9) + 6 <em>first </em><em>E</em><em>xponents</em>
25 - 2 × (-9) + 6 <em>next </em><em>M</em><em>ultiplication</em>
25 + 18 + 6 <em>next </em><em>A</em><em>ddition</em>
43 + 6 = 49